Suspended like an Absolon : brokeness and (dis)connections in Hart Crane’s proem : ’’To Brooklin Bridge’’ - Pires, Maria João (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
.